'The illusion of an authentic experience': a luster bowl in the Ashmolean Museum - Leoni, F; Norris, D; Domoney, K; Matin, M; Shortland, A (Brill Academic Publishers, 2019)
In 2014 the Ashmolean Museum conserved and examined one of the largest and most handsome ceramic vessels in its renowned Islamic art collection. An accomplished example of early thirteenth-century Persian lusterware from the bequest of Sir Alan Barlow, the salver had an unusually deformed profile and uneven wear that pointed at a number of past interventions. Some of these had already been uncovered in 2008 when the object was prepared for reinstallation in the revamped Ashmolean. However, it was only when analyzed by a team of inhouse specialists and scientists from Cranfield University and the Research Laboratory for Archaeology at the University of Oxford, that the extraordinary nature of its “restoration” could be assessed. This article presents the results of this collaborative effort and contributes important evidence to the thorny issue of the faking and forging of Islamic ceramics in the early twentiethc century, when collecting Islamic decorative arts was at its peak.